ANALYSING (1/125) 5^5 FRACTIONAL FACTORIAL DESIGNS AND SOME CONSIDERATIONS - CONAGIN, Armando; BARBIN, Décio; DEMÉTRIO, Clarice Garcia Borges; MORAL, Rafael de Andrade (Brazilian Journal of Biometrics, 2015)
In this paper we discuss some aspects of (1/125)5^5 fractional factorial designs and show how to analyze a simulated data set. We present the analysis of variance, the estimated coefficients of the regression model, the determination of maximum response and the economical analysis. We also discuss how to allocate the 25 treatments of (1/5)5^3 fractional factorials in completely randomized, incomplete block or incomplete latin square designs and the 25 treatments of (1/25)5^4 fractional factorials in incomplete block design. We present the R program to perform the analysis in the Appendix.